Determination of Activity Concentrations of the Naturally Occurring Radionuclides and the dose Rates from the Samples Collected from the Chittagong Urea Fertilizer Limited (CUFL), Bangladesh - M.M. Haque; M.M.H. Miah; Masud Kamal; A.K.M. Saiful Islam (The Global Environmental Engineers, 2016)
Abstract: The activity concentrations of 238U, 232Th and 40K have been determined for solid, liquid and product (urea) samples collected from the Chittagong Urea Fertilizer Limited (CUFL), Chittagong, Bangladesh. A total of 15 samples of different kinds were analyzed by using a calibrated high purity germanium (HpGe) detector of relative efficiency of 38%. For solid samples, the mean activity concentrations of 238U, 232Th and 40K have been found 78.67±2.87, 59.74±2.27 and 463.71±9.16 Bq/Kg, respectively. The mean activity concentrations of product samples for the corresponding radionuclide were 73.12±2.83, 74.59±2.32 and 391.58±9.38 Bq/Kg, respectively. For the case of liquid samples, the mean activity concentrations for the same nuclides were 25.09±1.71, 11.34±1.55 and 39.59±1.49 Bq/Kg, respectively. The artificial radionuclide 137Cs was not detected in any of the samples. The mean radiological hazard parameter values of outdoor absorbed dose rate, indoor absorbed dose rate, external radiation hazard, internal radiation hazard, annual effective dose equivalent, radium equivalent activity and representative level index were 95.72±9.04, 114.32±9.11 nGyh-1, 0.530±.05, 0.7±50.05, 113.59±11.41μSvy-1, 199.80±17.41 and 1.390±.14 Bq/Kg respectively, in solid samples. For the product samples, the mean values of the corresponding radiological indices were 97.10+9.71, 117.56+10.32 nGyh-1, 0.57±0.05 , 0.76±0.06, 119.50 ±11.72μSvy-1 , 209.50±17.72 and 1.50±0.14 Bq/Kg, respectively. Also in the liquid samples, the mean values for the corresponding radiological parameters were 18.43±2.69, 22.13±2.77 nGy.h−1, 0.12±0.03 , 0.19±0.05, 23.59± 2.36 μSvy1, 43.65±3.54 and 0.32±0.03 Bq/Kg, respectively. The obtained results of this study show that for some samples the values are lower and for the remaining are higher than the World average values. The mean representative index value is less than unity which confirms that the area is safe for the factory workers and the public nearby. The results can be used as a baseline data for further researchers.